Effective Visible Light Communication System for Underground Mining Industry - Ibrahim Mohammad Mansour (IAES Indonesian Section, 2020)
Adequate lightening and efficient communication technology have prime importance for safe underground mining communication system operations. Existing conventional light and communication systems used in underground mines are not very efficient solutions due to heavy power and maintenance requirements. Also, efficient communication technology is required for instantaneous reporting of any potential disaster event under hazardous underground environment. In this paper, we propose light fidelity (Li-Fi) as an efficient way of incident reporting as well as source of illumination for mines. Visible light communication (VLC) system is being used in mines operations, to support communication-blind areas. It exhibits superior performance over traditional radio frequency (RF) communication systems, in terms of low energy consumption, higher data rates achieved, and wide frequency band (430 − 790) T Hz. In this paper, we present VLC system for safe and reliable mining operations and analyze and discuss corresponding channel impulse response (CIR). We consider effect of shadowing and dust on our optical channel model. We compare the performance of our system with available methods in terms of bit error rate (BER), CIR, and prove the superiority of our proposed system.